ADAR1 mediated regulation of neural crest derived melanocytes and Schwann cell development - Nadjet Gacem (Nature Portfolio, 2020)
ADAR1 is an RNA editing protein known to regulate immune responses to dsRNA that has been connected to neural crest cell function. Here, the authors show RNA editing by ADAR1 is important for the normal development of neural crest derived melanocytes and Schwann cells.